THE (IN)EFFECTIVENESS OF REQUIRING PRIOR EXHAUSTION OF LOCAL REMEDIES IN INVESTMENT ARBITRATION - Smit, Samantha; Koen, Louis (Obiter, 2024)
The international investment-law regime continues to be mired in a legitimacy crisis that has given rise to important multilateral reform efforts through the United Nations Commission on International Trade Law. A key reform proposal is centred on the introduction of an exhaustion-of-local-remedies requirement. This article critically evaluates the exhaustion-of-local-remedies rule in the context of international investment law, and challenges its interpretation where such clauses already exist in contemporary investment law. The article concludes that investment tribunals have subverted these clauses in various ways, and considers the legal challenges states would need to address to best prevent the subversion of these clauses by investment tribunals in future.